2007
DOI: 10.1177/000313480707300721
|View full text |Cite
|
Sign up to set email alerts
|

Stapled Hemorrhoidopexy: Outcome Assessment

Abstract: Since its introduction as a new procedure for the surgical management of hemorrhoidal disease in 1993, stapled hemorrhoidopexy has become increasingly popular. This has been mostly the result of the reported reduction in postoperative pain. This study was designed to review retrospectively 152 patients combined from a 3-year period in a three-surgeon private colorectal practice and a 1-year period from an academic colon and rectal surgery training program. All patients had either grade II or III hemorrhoidal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
0
3
1
Order By: Relevance
“…Postoperative bleeding rate was 5.1% less than the 21.7% reported by Goldstein et al [29] with only 1 case needing reoperation. In this series, it was reported 1 case of potential life-threatening complication such as pararectal hematoma which has anyway a favorable course.…”
Section: Discussioncontrasting
confidence: 51%
“…Postoperative bleeding rate was 5.1% less than the 21.7% reported by Goldstein et al [29] with only 1 case needing reoperation. In this series, it was reported 1 case of potential life-threatening complication such as pararectal hematoma which has anyway a favorable course.…”
Section: Discussioncontrasting
confidence: 51%
“…In our study a minor group of patients accounting 1.1% reported faecal impaction. However, some of the studies have reported an occurrence of about 1% to 6.6% [25][26][27][28] . Though previous studies have reported higher recurrences following SH, in our study there was no cases of recurrence reported during the follow-up.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, Goldstein et al reported a postoperative bleeding rate of 21.7%, whereas Festen et al observed persistence and recurrence of prolapse at a rate of 16%. [24,25] In South Korea, purse-string suturing is typically performed at a lower level during SH than the level predominantly used in other countries, with the aim of reducing recurrence rates and achieving a better anal appearance after surgery. [26] In our institution, lower purse-string levels are preferred during PSH.…”
Section: Discussionmentioning
confidence: 99%